THE MISSION STATEMENT OF THE BUSINESS ORGANISATION BY REFERENCE TO THE ECONOMIC MARKET REQUIREMENTS - Marius Costel EȘI (USV Annals of Economics and Public Administration, 2014)
Acting as a systemic entity, the business organization, viewed as an aggregate, involves at the functional level, the assumption of an approach that relates to the idea of legitimacy within the current economic pragmatism. At the same time, dynamics of the economic reality highlight methodological explanations regarding the role and the functions of a manager at organizational level. However, the managerial functions within the business organization`s frame of reference can be corroborated with the formulated contents of the company's stated mission and vision. In other words, the existence of an implementation of managerial strategies process does nothing but reveal the way in which a specific managerial philosophy (epistemology) proves itself useful in the of economics operational field. We note that an analysis of the way in which the business organization`s mission is formulated can be materialized in the conditions in which it is reported to the actual requirements of economic markets. Consequently, our attention focuses on the conceptual - theoretical, but also on the practical valences of the two dimensions encountered in the enunciation and definition of the business organization`s mission: the strategies and the objectives set by (managerial) decision makers. In addition, the substantiation of this scientific research aims, in this context, to an epistemological analysis of the understanding and explicitation process concerning the idea of mission within a business organization`s system. We consider that this methodological substantiation finds its full justification to the extent that this evaluation of a business mission idea implies a reference to the managerial authorities` skills, but also to the need of economic education, focused on economic aspects of financial nature. An important role in the ininitiated approach is held by the idea of economic reassessment of the "need", "requirement" and "demand" concepts. Therefore, the methodological issue under discussion reveals an explanatory endeavour that legitimizes the suppositions pertaining to the acceptance of an economic pragmatism within a knowledge society.